2019
DOI: 10.1111/anae.14637
|View full text |Cite
|
Sign up to set email alerts
|

The TotaltrackTM video laryngeal mask: an evaluation in 300 patients

Abstract: The Totaltrack TM is a new video laryngeal mask, which combines a supraglottic airway with a videolaryngoscope. We evaluated the performance of this device in an observational study in 300 adult patients. The Totaltrack was inserted at the first attempt and the glottis seen in all cases. In 249 patients (83%; 95%CI 78.7-87.3%) the glottis was seen at the first attempt. Adequate ventilation and tracheal intubation were achieved in all patients. The median time to visualisation of vocal cords, to confirmation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…In a series of eleven patients, the TotalTrack served as a rescue device for oxygenation and tracheal intubation in failed laryngoscopic, videolaryngoscopic, or fiberoptic intubation [43]. Recent large prospective assessment of the device on 300 patients confirmed the previous studies, showing a 100% insertion success rate, 85% success of tracheal intubation at the first attempt, and all patients were intubated through the device after re-positioning [44].…”
Section: Clinical Evidencementioning
confidence: 79%
“…In a series of eleven patients, the TotalTrack served as a rescue device for oxygenation and tracheal intubation in failed laryngoscopic, videolaryngoscopic, or fiberoptic intubation [43]. Recent large prospective assessment of the device on 300 patients confirmed the previous studies, showing a 100% insertion success rate, 85% success of tracheal intubation at the first attempt, and all patients were intubated through the device after re-positioning [44].…”
Section: Clinical Evidencementioning
confidence: 79%
“…We graded the images of 100 patients. Totaltrack mask can only visualize the glottis in 83% of patients [ 9 ]. LMA Ctrach, another video laryngeal mask, can expose the glottis in 85% of patients after manual adjustment [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both systems allow simultaneous ventilation and intubation under direct vision but lack the adaptability to the pharyngeal dimensions of the patient's anatomy. A recent study using the TotalTrack VLM on 300 patients showed glottic visualisation in 83% and first attempt successful intubation in 85% of the studied patient [22]. However no studies are available that compare this device with other SADs.…”
Section: Other Sads With Integrated Videoscopementioning
confidence: 99%